KARAKTERISTIK TANAH PADA LAHAN TIDUR UNTUK PERTANIAN DI KENAGARIAN JORONG DURIAN KAMANG MUDIAK KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Ulfa, Rahmawati; Edial, Helfia; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
This research aims to study, reveal, analyze and interpret data on soil characteristics (texture, permeability, organic matter, soil pH) on vacant land in Kenagarian Kamang Mudiak Kamang Magek Agam District. Based on field research and discussion of the results of hypothesis testing results are obtained as follows: the results obtained on the sample texture 1 7.60%, 51.81% of dust, clay loam texture class 40.59 dusty. Permeability of 0.14 cm / h rather low grade and grade ny 5.95 pH slightly acidic, organic matter is very high-class 18.050%, grained structure in the sample is a proper cultivation of the corn crop and good for growth because of its structure for processing or planted with maize crops. Results obtained on sample 2 7.72% the texture of sand, dust 65.76%, 26.52% clay, sandy clay class, permeability of 5.86 cm / h, pH 6.01 grade slightly sour and organic matter 19.48% very high grade soil crumb structure in this sample would make the cultivation of corn plants, but growth is not good for the corn crop. 3 samples obtained at 6.24% textured sand, dust 53.45%, 40.31% clay loam texture berliat berliat loam texture, permeability of 1.02 cm / hr bnya class rather low, slightly acid pH of 5.46 classes, materials 21.34% organic with very high grade blocky structure in this sample would make a corn crop cultivation but grow poorly because of the structure of the soil if the blocky blocky structure the corn crop cultivation is not good.